A Unified MPC Envelope Control Formulation for Toyota Guardian and Chauffeur. Issue 16 (2022) - Bobier-Tiu, Carrie G.; Koehler, Sarah M.; Brown, Matthew; Ahumada, Manuel
Abstract: For a vehicle that can execute safety and autonomy technologies in two paradigms — shared control (Guardian) and autonomous control (Chauffeur) — we present a unified formulation for chassis control in both paradigms. The primary goal for both is to maintain the vehicle within a safe state space, and secondarily track either a human driver's intention through shared control, or a desired trajectory in autonomous operation. We introduce the notion of a pseudo-driver when in the autonomous mode, which mathematically mimics the human driver by using the desired path to generate a "driver's" steering angle and acceleration commands. This pseudo-driver allows for an identical controller formulation between both modes. Quantified experimental results are presented.